Growth hormone-releasing hormone receptor signaling in experimental ocular inflammation and neuroprotection - Ling-Ping Cen; Tsz Kin Ng; Wai Kit Chu; Chi Pui Pang (Neural Regeneration Research, 2022)
Both inflammation and anti-inflammation are involved in the protection of retinal cells. Antagonists of the hypothalamic growth hormone-releasing hormone receptor (GHRHR) have been shown to possess potent anti-inflammatory properties in experimental disease models of various organs, some with systemic complications. Such effects are also found in ocular inflammatory and neurologic injury studies. In experimental models of mice and rats, both growth hormone-releasing hormone receptor agonists and antagonists may alleviate death of ocular neural cells under certain experimental conditions. This review explores the properties of growth hormone-releasing hormone receptor agonists and antagonists that lead to its protection against inflammatory responses induced by extrinsic agents or neurologic injures in ocular animal models.